MASALAH PSIKOSOSIAL PADA LANJUT USIA - Kartinah Kartinah; Agus Sudaryanto (Universitas Muhammadiyah Surakarta, 2008)
Elderly population now is tenderly to be higher than 5 or 10 years ago. In the future population of elderly people in Indonesia will in high amount. The great number of elderly population in this nation have some consequency for example: economic, social, demografik, and helath care system. Ministry of Health have program to maintain health status of elderly people. One of common health problem in elderly was psikososial problem. Elderly people can suffer from many psikososial problem. Psikosial problem in elderly is varied, for example : depression, low of support system from family and society, Dimensia and other health problem. Nurses as helath care personil must aware about psikososial aspect or psikososial problem in elderly, so they can give some direction to family or society.